Systematic review on prevalence of Cerebral Palsy - Imtiaz, Khkula; Khan, Wassam Akbar; Ullah, Ghazanfar; Yousafzai, Yasar; Darain, Haider (Annals of Allied Health Sciences, 2017)
Aims: The objective of this review is to provide a collective form of data on prevalence of cerebral palsy and the ratio of CP related to birth weight of infants. Methods: A systematic review was conducted by utilizing PRISMA (Preferred Reporting Items for Systematic Review and Meta-analyses) declarations. Cross sectional retrospective descriptive study and population based CP registry were used and the data were collected in the respective studies of review, using computer records and parental questionnaires. Statistical analysis was carried out by using SPSS version 20. Results: A total of 10 studies were selected to conduct the review. The overall ratio of CP is 2.5 per 1000 live births. For the infants with very low birth weight of less than 1500g, the CP prevalence showed highest proportion. Conclusion: This view has been performed following these articles regarding the prevalence of CP in different localities of the world. These studies outlined some variables which enhances the knowledge about different aspects of CP